The Observing the methods of teaching between the good man Khidr and Prophet Moses in surah Al-Kahf in the Holy Qur’an - Mustafa, Hawkar Aziz; Rafeeq, Shwan Gluk (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2025)
ABSTRACT This article shows methods of teaching between the good man and Moses in surah Al-Kahf in the Holy Qur’an. There are several methods of teaching that appear between the good man and Moses. Some of the methods are vividly mentioned and there might be other hidden methods. Today, this conversation between the good man and Moses in the Holy Qur’an is well-appreciated by Muslims and their scholars and is widely read and extract knowledge everywhere: in mosques, Islamic schools and universities, because this Surah is extremely effective not only in terms of gaining knowledge among Muslim scholars, but also in terms of the finding the right method for small group of students, personal skills and the expansion of the character of learners. It is important that several teaching methods can be found to approximately all forms of methods of teaching: in one-to-one teaching, field trip and direct method in language learning. The research observed the participation of learners in direct method in relation to language learning.